THE EFFECT OF PRENATAL YOGA ON LENGTH OF LABOR IN THE ACTIVE PHASE OF PRIMIGRAVIDA: THE EFFECT OF PRENATAL YOGA ON LENGTH OF LABOR IN THE ACTIVE PHASE OF PRIMIGRAVIDA - Setiana Andarwulan; Annah Hubaedah (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Labor begins with the process of opening and effacement of the cervix. Opening and thinning depends on the contraction that occurs. More frequent contractions will speed up labor. If the contractions slow down, the length of labor will be slower. One effort to improve contractions is by doing body movements or light exercise through prenatal yoga. Prenatal yoga is an exercise program for healthy pregnant women to prepare the mother's physical condition by maintaining the condition of the muscles and joints that play a role in the birthing process. Objectives: the type of research carried out is quantitative research, with an experimental research design. The research design is in the form of a two group pre test and post test design. The population consisted of 50 primigravida pregnant women. The research sample was 40 respondents. With a sampling technique in the form of purposive sampling. The 40 respondents were divided into two groups, namely the RND control group and the Prenatal Yoga experimental group. Methods: Data analysis using univariate techniques in the form of frequency distribution and bivariate using the Shapiro Wilk test and independent T test Results: Data analysis using frequency distribution showed that the age of the research subjects ranged from 18-30 years, where the average age of the Prenatal Yoga group was slightly older than the RND group. Bivariate data analysis shows that the Independent Sample Test Results are ρ=2.11. Conclusions: There is a significant difference in the length of the first stage of labor in the active phase in primigravida between Prenatal Yoga and RND. So the use of prenatal yoga needs to be developed and given to mothers who are about to give birth.